Laser-assisted ablation of UiO-66 metal-organic framework on the PET surface for novel electrode materials - Kogolev D. A. Dmitry Anatoljevich; Semyonov O. V. Oleg Vladimirovich; Fatkullin M. I. Maksim Ilgizovich; Guselnikova O. A. Olga Andreevna; Postnikov P. S. Pavel Sergeevich (2022, 2022)
Title screen